Aluminium-matrix nanocomposites: swarm-intelligence optimization of the microstructure and mechanical properties - Shabani, Mohsen Ostad (Materiali in tehnologije, 2012)
In the present research, ceramic nanoparticles were added to the Al-Si aluminum alloy using the casting method. Experimental characterization of the mechanical properties showed that an incorporation of the nanoparticles improved the hardness and strength of the composites. This paper also reports a successful development of an effective approach based on the combination of a parallel particle-swarm optimization and FEM methods to determine the optimum conditions of the Al-matrix nanocomposites in terms of the microstructure and mechanical properties. It has been shown that a parallel particle swarm performs well in the optimization of nanocomposite materials.
Keywords: vzporedni roji delcev; nanokompoziti; aluminijeve zlitine; aluminium alloy; mehanske lastnosti